Galatians : a commentary - Boer, Martinus C. de (Martinus Christianus), 1947- (New Testament library., 2011)
This commentary in the New Testament Library series is not a systematic study of Pauline theology; rather, the aim of this study is to trace Paul's theology as it unfolds in his letter to the church at Galatia, and to attempt to illuminate, as far as possible, how the Galatians likely comprehended it, at the time they received it. The author asks readers to imagine themselves as silent witnesses to Paul's dictation of the letter and to observe, through a historical perspective, how the Galatian Christians might have understood Paul's words.--From publisher's description.